Additive manufacturing for designers : a primer - Elliott, Amy; Waters, Cynthia (SAE International, 2019)
Discusses the topics needed for designers to gain a holistic understanding of the micro and macro components of the world of AM, or 3D printing. The book offers a brief history of AM, a discussion of the difference between rapid prototyping and AM, and standard terminology for each type of AM technology. The role and impact of standards is also presented.